Developmental changes in sensitivity to spatial and temporal properties of sensory integration underlying body representation - Greenfield, Katie; Ropar, Danielle; Themelis, Kristy; Ratcliffe, Natasha; Newport, Roger (2017)
The closer in time and space that two or more stimuli are presented, the more likely it is that they will be integrated together. A recent study by Hillock-Dunn and Wallace (2012) reported that the size of the visuo-auditory temporal binding window — the interval within which visual and auditory inputs are highly likely to be integrated — narrows over childhood. However, few studies have investigated how sensitivity to temporal and spatial properties of multisensory integration underlying body representation develops in children. This is not only important for sensory processes but has also been argued to underpin social processes such as empathy and imitation (Schütz-Bosbachet al., 2006). We tested 4 to 11 year-olds’ ability to detect a spatial discrepancy between visual and proprioceptive inputs (Experiment One) and a temporal discrepancy between visual and tactile inputs (Experiment Two) for hand representation. The likelihood that children integrated spatially separated visuo-proprioceptive information, and temporally asynchronous visuo-tactile information, decreased significantly with age. This suggests that spatial and temporal rules governing the occurrence of multisensory integration underlying body representation are refined with age in typical development